Asymmetry of Hippocampal Tau Pathology in Primary Age-Related Tauopathy and Alzheimer Disease. Issue 5 (15th April 2021) - Walker, Jamie M; Fudym, Yelena; Farrell, Kurt; Iida, Megan A; Bieniek, Kevin F; Seshadri, Sudha; White, Charles L; Crary, John F; Richardson, Timothy E
Abstract: Primary age-related tauopathy (PART) is a neurodegenerative entity defined as neurofibrillary degeneration generally restricted to the medial temporal region (Braak stage I–IV) with complete or near absence of diffuse and neuritic plaques. Symptoms range in severity but are generally milder and later in onset than in Alzheimer disease (AD). Recently, an early predilection for neurofibrillary degeneration in the hippocampal CA2 subregion has been demonstrated in PART, whereas AD neuropathologic change (ADNC) typically displays relative sparing of CA2 until later stages. In this study, we utilized a semiquantitative scoring system to evaluate asymmetry of neurofibrillary degeneration between left and right hippocampi in 67 PART cases and 17 ADNC cases. 49% of PART cases demonstrated asymmetric findings in at least one hippocampal subregion, and 79% of the asymmetric cases displayed some degree of CA2 asymmetry. Additionally, 19% of cases revealed a difference in Braak score between the right and left hippocampi. There was a significant difference in CA2 neurofibrillary degeneration (p = 0.0006) and CA2/CA1 ratio (p < 0.0001) when comparing the contralateral sides, but neither right nor left was more consistently affected. These data show the importance of analyzing bilateral hippocampi in the diagnostic evaluation of PART and potentially of other neurodegenerative diseases.